Reliable leak detection in a heat exchanger of a sodium-cooled fast reactor. (July 2020) - Guépié, Blaise Kévin; Grall-Maës, Edith; Beauseroy, Pierre; Nikiforov, Igor; Michel, Frédéric
Highlights: Monitoring of a sodium-cooled fast reactor heat exchanger. Detection of water or nitrogen leaking into a sodium circuit. Abrupt changes in the spectral density of vibro-acoustic signals. Analytical formulas for the statistical properties of the detector. Abstract: The heat exchanger (HE) should be permanently monitored in order to detect water or nitrogen leaking into a sodium circuit, which can affect the sodium-cooled fast reactor (SFR) performance or safety. The HE must be shut down in a few seconds after the beginning of the leak, even very small, and repaired. The solution developed in the paper is based on the reliable detection of abrupt changes in the spectral density of measured vibro-acoustic signals. The main difficulty lies in the fact that the small HE leaks have to be detected in the presence of high normal operating noise coming from different equipment (pumps, turbine, etc.). The records from experimental mock-ups dedicated to sodium-gas HE studies and installed at the Commissariat à l'energie atomique et aux energies alternatives (CEA) have been used to assess the proposed solution. The significance of this research with respect to the previous works is twofold. First, the proposed solution detects a small leak in the sodium-gas HE with the signal-to-noise ratio SNR ⩾ - 30 dB provided that the detection delay is upper bounded by 60 s, the probability of missed detection is upper bounded by 10 - 5 and the probability of false alarm (per hour) is upper bounded by 10 - 5 h - 1, which is much better than the usually requested SNR of - 17 dB. Second, the analytical formulas for calculation of the probabilities of missed detection and false alarm have been proposed that guarantees the required statistical properties of the proposed test.